A PENERAPAN EDUCATION AND SUPPORT GROUP TERHADAP KUALITAS HIDUP PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH PUSKESMAS DARUL AZHAR: PENERAPAN EDUCATION AND SUPPORT GROUP TERHADAP KUALITAS HIDUP PASIEN DIABETES MELLITUS TIPE 2 DI WILAYAH PUSKESMAS DARUL AZHAR - Susanti, Novia; Rizkiansyah (WELL BEING, 2024)
In Indonesia and the world, it is predicted that the number of diabetes mellitus sufferers will increase every year. Patients with diabetes mellitus not only have physical problems but also psychological problems, this is because the complications that arise, both acute and chronic, cause changes in the sufferer's quality of life. Various approaches have been taken to overcome this problem, one of which is by providing education and support groups. This research uses a pre-experimental design with a pre-post-test one-group design approach. This research was conducted in 4 meetings over 1 month with a sample size of 27 people suffering from type II diabetes mellitus. Sample selection used a purposive sampling technique. The instruments used were the Diabetes Quality of Life (DQOL) questionnaire and the education and support group module. The analysis used uses an alternative test, namely the Wilcoxon test. The research results showed that the p-value was 0.000 <0.05, so H0 was rejected and H1 was accepted. The conclusion from the results of this research is that there is an influence of education and support groups on the quality of life of type II diabetes mellitus patients.